Derivation of flow related risk indices for stenosed left anterior descending coronary arteries with the use of computer simulations. Issue 9 (September 2016) - Papadopoulos, Konstantinos P.; Gavaises, Manolis; Pantos, Ioannis; Katritsis, Demosthenes G.; Mitroglou, Nicholas
Highlights: We constructed coronary models of different complication risk. We performed transient numerical simulation of the flow in each model. We identified differentiation of suspicious flow patterns among the models. The observed differentiation was expressed via arithmetic risk indices. Abstract: The geometry of the coronary vessel network is believed to play a decisive role in the initiation, progression and outcome of coronary artery disease (CAD) and the occurrence of acute coronary syndromes (ACS). It also determines the flow field in the coronary artery which can be linked to CAD evolution. In this work geometric 3D models of left anterior descending (LAD) coronary arteries associated with either myocardial infarction (MI) or stable (STA) CAD were constructed. Transient numerical simulations of the flow for each model showed that specific flow patterns develop in different extent in the different groups examined. Recirculation zones, present distal the stenosis in all models, had larger extent and duration in MI cases. For mild stenosis (up to 50%) areas with low time averaged wall shear stress TAWSS (<0.15 Pa) as well as areas with high TAWSS (>3 Pa) appeared only in MI models; in moderate and severe stenosis (>50%) these areas were present in all models but were significantly larger for MI than STA models. These differentiations were expressed via numerical indices based on TAWSS, oscillating shear index (OSI) and relative residence time (RRT). Additionally we introduced the coagulation activation index (CAI), based on the threshold behaviour of coagulation initiation, which exceeded the suggested threshold only for MI models with intermediate stenosis (up to 50%). These results show that numerical simulations of flow can produce arithmetic indices linked with the risk of CAD complications.